2016
DOI: 10.1111/bjc.12109
|View full text |Cite
|
Sign up to set email alerts
|

Worry processes in patients with persecutory delusions

Abstract: Worry is a significant concern for patients with paranoia Worry in paranoia is likely to be caused by similar mechanisms as worry in emotional disorders The results support the recent trial findings that standard techniques for treating worry in anxiety, suitably modified, are applicable for patients with paranoia LIMITATIONS: The findings are limited by the self-report nature of measures and by the study design which precludes any assumptions about the direction of causality between the psychological mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Most studies employed a cross‐sectional design and relied on self‐report measures of worry. One cross‐sectional study ( N = 150) found that self‐reported rumination was associated with more paranoid thoughts ( r = .33, p < .01) and more delusions ( r = .48, p < .01; Startup et al, 2016). However, these associations were rendered not significant after adjusting for self‐reported worry and anxiety symptoms (Startup et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies employed a cross‐sectional design and relied on self‐report measures of worry. One cross‐sectional study ( N = 150) found that self‐reported rumination was associated with more paranoid thoughts ( r = .33, p < .01) and more delusions ( r = .48, p < .01; Startup et al, 2016). However, these associations were rendered not significant after adjusting for self‐reported worry and anxiety symptoms (Startup et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…One cross‐sectional study ( N = 150) found that self‐reported rumination was associated with more paranoid thoughts ( r = .33, p < .01) and more delusions ( r = .48, p < .01; Startup et al, 2016). However, these associations were rendered not significant after adjusting for self‐reported worry and anxiety symptoms (Startup et al, 2016). Seven studies were included in the meta‐analysis as they reported correlation coefficients between rumination and positive symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive models of paranoia [58][59][60] cite worry and anxiety as maintaining paranoid ideation based on a range of prior evidence. Worry has been found to be present at high levels in highly paranoid people [61], and psychological treatment for worry has been shown to reduce paranoia in a targeted randomized controlled trial [62]. Similarly, induction of stress has been shown to increase state paranoia, mediated by anxiety [6,56], in addition to anxiety predicting higher state paranoia in ambiguous virtual environments [63].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive models of paranoia (59)(60)(61) cite worry and 532 anxiety as maintaining paranoid ideation based on a range of prior evidence. Worry 533 has been found to be present at high levels in in highly paranoid people (62) and 534 psychological treatment for worry has been shown to reduce paranoia in a targeted 535 randomised controlled trial (63). Similarly, induction of stress has been shown to 536 increase state paranoia, mediated by anxiety (6,57), in addition to anxiety predicting 537 higher state paranoia in ambiguous virtual environments (64).…”
Section: Discussion 492mentioning
confidence: 99%